2004
DOI: 10.2527/2004.82113302x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of consumer sensory acceptance and value of domestic beef steaks and steaks from a branded, Argentine beef program1,2

Abstract: To determine consumer sensory acceptance and value of branded, Argentine (grass-finished, aged 30+ d) and domestic (U.S. grain-finished beef, aged 9 d) strip loins were paired based on similar Warner-Bratzler shear force values (P = 0.34) and similar marbling levels (P = 0.82). Consumers in Chicago, IL, and San Francisco, CA (n = 124 per city), evaluated one pair of Argentine and domestic steaks, and had the opportunity to participate in a silent, sealed-bid auction to purchase steaks matching the taste panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 13 publications
4
34
0
4
Order By: Relevance
“…These results align with previous reports that U.S. consumers were willing to pay more for domestic U.S. grain finished beef when compared to imported beef from countries such as Australia, Canada, and Argentina, where finishing practices differ from those in the U.S. (Killinger et al, 2004;Sitz et al, 2005). Killinger et al (2004) found that U.S. consumers were willing to pay more for U.S. beef compared to grassfed Argentine beef, and they were willing to pay even more when they found domestic samples more acceptable than Argentine steaks.…”
Section: Willingness To Paysupporting
confidence: 82%
See 1 more Smart Citation
“…These results align with previous reports that U.S. consumers were willing to pay more for domestic U.S. grain finished beef when compared to imported beef from countries such as Australia, Canada, and Argentina, where finishing practices differ from those in the U.S. (Killinger et al, 2004;Sitz et al, 2005). Killinger et al (2004) found that U.S. consumers were willing to pay more for U.S. beef compared to grassfed Argentine beef, and they were willing to pay even more when they found domestic samples more acceptable than Argentine steaks.…”
Section: Willingness To Paysupporting
confidence: 82%
“…Killinger et al (2004) found that U.S. consumers were willing to pay more for U.S. beef compared to grassfed Argentine beef, and they were willing to pay even more when they found domestic samples more acceptable than Argentine steaks. Likewise, Sitz et al (2005) reported that consumers would pay $1.20/0.45 kg more for domestic strip steak compared to Australian grass-fed strip steak, but only a $0.38/0.45 kg premium for U.S. beef over Canadian beef.…”
Section: Willingness To Paymentioning
confidence: 96%
“…Research in meat science has also revealed additional factors that cause meat to be more or less desirable, such as age of the animal, species, muscle cut, post-fabrication handling, and cooking method (Smith et al 1974;Paterson et al 1987;Spanier et al 1997;Miller 2001;Calkins and Hodgen 2007). In addition, sensory research on American consumers indicates that consumers become accustomed to certain meat flavor profiles, and they rate those familiar samples higher for overall acceptability and value (Killinger et al 2004;Sitz et al 2005Sitz et al , 2006.…”
Section: Meat Sciencementioning
confidence: 94%
“…Some consumers will find this degree of doneness ok, others will find it under-cooked and others over-cooked. In recent published studies of beef steak, samples often have been cooked to an internal temperature of 71 ± 1°C in both consumer acceptance studies (Killinger, Calkins, Umberger, Feuz, & Eskridge, 2004;Oliver et al, 2006) and studies by trained panels (Yancey, Dikeman, Hachmeister, Chambers, & Milliken, 2005;Yancey et al, 2006). However, research studies of meat products have ranged from 63°C for beef steaks (Campbell, Hunt, Levis, & Chambers, 2001) to 80°C for ground meat (Chun, Chambers, & Chambers, 2005).…”
Section: Introductionmentioning
confidence: 98%